The GWIPS‐viz Browser. Issue 1 (16th May 2018) - Kiniry, Stephen J.; Michel, Audrey M.; Baranov, Pavel V.
Abstract: GWIPS‐viz is a publicly available browser that provides Genome Wide Information on Protein Synthesis through the visualization of ribosome profiling data. Ribosome profiling (Ribo‐seq) is a high‐throughput technique which isolates fragments of messenger RNA that are protected by the ribosome. The alignment of the ribosome‐protected fragments or footprint sequences to the corresponding reference genome and their visualization using GWIPS‐viz allows for unique insights into the genome loci that are expressed as potentially translated RNA. The GWIPS‐viz browser hosts both Ribo‐seq data and corresponding mRNA‐seq data from publicly available studies across a number of genomes, avoiding the need for computational processing on the user side. Since its initial publication in 2014, over 1885 tracks have been produced across 24 genomes. This unit describes the navigation of the GWIPS‐viz genome browser, the uploading of custom tracks, and the downloading of the Ribo‐seq/mRNA‐seq alignment data. © 2018 by John Wiley & Sons, Inc.